Identitas nasional: Peran generasi muda dalam memperkuat identitas nasional di era globalisasi - Nabila, Siti (Maliki Interdisciplinary Journal, 2025)
In the era of complex globalization that affects various cultures and global aspects, the essence of national identity as a pride that needs to be maintained and preserved. It is necessary to adopt Pancasila to raise awareness of how important it is to maintain the values and teachings of the Indonesian nation, especially among young people, who are often influenced by the appeal of Western culture. The younger generation has an important role in maintaining national identity by using local products and through citizenship education. Therefore, to build a strong nation and state, it is important to foster and preserve every teaching and cultural value. Instilling national values ​​from an early age through formal and non-formal education is a strategic step in strengthening national identity. A curriculum that integrates character education, national history, and Pancasila values ​​can form a collective awareness of the younger generation regarding the importance of loving and maintaining national identity.